The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District: The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District - Muhammad Ma'ruf; Arif Budi Setianto; Rindi Ibrahim Lasanudin; Sapto Yuliani (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Diabetes mellitus is a disease that is often called "the silent killer." This disorder occurs in the metabolism of carbohydrates and fats that are relatively deficient in insulin in the body. Previous research said that coffee could be used as a therapy for diabetes mellitus. The background for writing this article is the high prevalence of knowledge and attitude of coffee lovers and scientific evidence of coffee content as a decrease in blood glucose levels. Objectives: This study aims to describe the knowledge and attitude of coffee lovers toward diabetes mellitus in coffee shops in Palaran District. Research Metodes: This research method uses quantitative and descriptive. Data were obtained by distributing questionnaires to research subjects, namely coffee lovers who were in coffee shops in the Palaran District, Samarinda City, totaling 46 respondents. Results: The results showed that there were 26 coffee lovers (56.5%) who had good knowledge of diabetes mellitus and 20 people (43.5%) who had a good understanding of diabetes mellitus. Meanwhile, in the attitude of coffee lovers, there were 35 people (76.1%) who had good attitude towards diabetes mellitus and 11 people (23.9%) who had a reasonably good attitude towards diabetes mellitus. Conclusion: It can be concluded that the coffee lovers in the Palaran District coffee shop, on average, have good knowledge and attitude towards diabetes mellitus.